365 TELEMEDICINE IN PEDIATRIC SEXUAL ASSAULT. Issue 1 (1st January 2007) - MacLeod, K. J.; Boyle, C.; Miyamoto, S.; Marcin, J. P.; Rogers, K. K.
Abstract : Rates of child abuse are high in rural Northern California, where the hospitals have fewer resources and less experienced pediatric sexual assault examiners. Without access to a complete, accurate examination, child sexual abuse victims face unnecessary admission or transfer and may not receive the quality of care that they deserve, putting them at risk for inadequate protection and continued abuse. The goal of this research project is to use live telemedicine consultations to improve the quality of care provided to child sexual assault victims in rural areas. We hypothesize that telemedicine will increase the ability of the rural provider to perform a complete and accurate sexual assault examination. The University of California, Davis (UCD), Children's Hospital, CAARE Center, and the UCD Center for Health and Technology joined forces to provide telemedicine consultations to clinicians in two rural hospitals. Child abuse experts from UCD provide 24-hour-a-day live, pediatric sexual assault consultations, assisting in both the examiantion and the interpretation of the findings. Rural provider education and training are included. We designed and implemented quality of care surveys to assess patient history, physical examination, colposcopic and manual manipulation techniques, interpretation of findings, and treatment plans for these children. Data from the first 25 cases of live, telemedicine consultation showed that the mean duration for completing the consults was 58.89 minutes; with a range of 25 to 90 minutes. These consultations also showed that the telemedicine intervention produced the following: 44% positive change in history and data gathering; 77% changed their examination to include the use of the multimethod examination technique; and 52% changed their methods to include the use of adjunct techniques. The use of the multimethod and adjunct techniques during sexual assault examination has been shown, in previous studies, to improve the accuracy and completeness of these examinations. There were four acute sexual assault examination consultations that required additional methods in the collection of forensically defensible evidence. In these cases, the telemedicine consultation resulted in the UCD child abuse experts assisting the rural providers in the use of the Woods lamp (instrument with ultraviolet light to illuminate bodily secretions), as well as the proper collection and packaging of secretions and hair for possible DNA analysis. In conclusion, the use of telemedicine in cases of pediatric sexual assault increases the quality of care offered by rural health care providers to young victims in isolated communities.